(untitled) (Research, Society and Development, 2020)
The intestinal microbiota of birds presents a wide variety of commensal microorganisms distributed from the crop, permeating through the duodenum, jejunum, ileum, caecuses and colon. They act in the metabolism of nutrients in the diet, generating important products for the balance of the microbiome and preservation of the intestinal organs tissue wall, resulting in better yield, nutritional development of the birds and satisfactory productivity for the producer. The guarantee of such results is only possible when there is knowledge about the microbiome, the nutritional requirements of the birds, the quantity and adequate time for food supply, environmental conditions and water supply. These are important points in this process of maintaining the symbiosis between host and microorganisms. This literature review aims to point out the main aspects of the intestinal microbiota of production birds, elucidating the intestinal anatomy of birds, contributing to the productive performance with emphasis on the set of commensal microorganisms present, elucidating the products resulting from the performance of these agents and which additives performance improvement has been used in animal nutrition to guarantee the health of the microbiome, based on the main agents present in the gastrointestinal tract of birds of zootechnical interest.